1980
DOI: 10.1677/joe.0.0870073
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Regulation of Calcitonin in Serum of Old and Young Buffalo Rats

Abstract: Studies were carried out to characterize the secretion and the effects of calcitonin in the Buffalo rat. Mean basal concentrations of calcitonin and parathyroid hormone were significantly increased in serum of rats older than 6 months of age as compared with rats between 2 and 3 months of age. The mean concentration of calcium in serum was independent of age. In both age groups, serum calcitonin was increased by administration of calcium (1 mmol/kg body wt) or isoproterenol (100 microgram/kg body wt), was dimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1982
1982
1995
1995

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…We also made the novel observation that in male F344 rats circulating PTH increases with advancing age. In a less rigorous study in terms of aging, Queener et al (1980) have also reported that the serum PTH of "young Buffalo rats" between 2 and 3 months of age was lower than that of "old rats" 6 months of age or older. The age-related increase in circulating PTH observed in our study was not associated with a decrease in serum calcium or alterations in serum proteins (not reported).…”
Section: Discussionmentioning
confidence: 99%
“…We also made the novel observation that in male F344 rats circulating PTH increases with advancing age. In a less rigorous study in terms of aging, Queener et al (1980) have also reported that the serum PTH of "young Buffalo rats" between 2 and 3 months of age was lower than that of "old rats" 6 months of age or older. The age-related increase in circulating PTH observed in our study was not associated with a decrease in serum calcium or alterations in serum proteins (not reported).…”
Section: Discussionmentioning
confidence: 99%
“…In rats, serum concentrations of both immunoreactive PTH and calcitonin (Queener, Bell, Larson et al 1980;Armbrecht, Forte & Halloran, 1984 ) increase with age, but serum l,25-(OH)2D declines with age (Gray & Gambert, 1982;Armbrecht et al 1984 ). In man, serum 1,25-(OH)2D also declines with age (Gallagher, Riggs, Eisman et al 1979) despite a rise in serum PTH (Gallagher, Riggs, Jerpbak & Arnaud, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in the rat, serum immunoreactive CT is increased by isoproterenol and decreased by propranolol [10]. On the other hand, changes in serum PTH and plasma CT, in response to alteration of serum calcium produced by calcium and EDTA, were not altered following chemical sympathectomy by 6-hydroxydopamine in that species [11].…”
Section: Introductionmentioning
confidence: 85%